Stable or changing well-being? Daily hassles and life satisfaction of Czech adolescents over the last three decades - Macek, Petr; Ježek, Stanislav; Lacinová, Lenka (Frontiers in Psychology, 2022)
While the assumption that the sociopolitical end economic situation affects adolescents' well-being, encompassing life satisfaction and a positive sense of self, is plausible, few studies have confirmed such macrosocial influences. The case of the Czech Republic offers an example of a society transitioning from totalitarian government (from 1989) to western democracy. Our study provides a statistical description of Czech adolescents’ well-being over the past thirty years in association with the subjective perception of everyday problems. These daily hassles represent experiences and conditions of daily living that have been appraised as salient and harmful or threatening to adolescents’ well-being. We analyzed four samples of adolescents aged 14-17 years surveyed at four-time points over the last three decades - 1992, 2001, 2011, and 2019, total N = 4005 (1992: 255, 2001:306, 2011:363. 2019: 3081, 54.6 % females). The results show that life satisfaction, self-esteem, and self-reported daily hassles changed only marginally from 1992 to 2019 with small differences related to the post-revolution 1992 cohort. Adolescents reported increasing problems in school, relationships with parents, sports, and leisure time over the study period. A model linking daily hassles to life satisfaction across four cohorts showed that daily hassles strongly predicted life satisfaction except in the post-revolution cohort of 1992 when life satisfaction was also the lowest. Across the cohorts, gender differences in life satisfaction changed from males being more satisfied in 1992 to females being more satisfied in 2019. Limitations stemming from sampling differences across cohorts are discussed.